AN ANALYSIS OF THE WRITING ANXIETY OF THE FOURTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU IN WRITING ESSAYS - Reni Andini; Fadly Azhar; Rumiri Aruan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is aimed to find out the writing process which makes the fourth semester students of English Study Program FKIP Universitas Riau feel anxious in writing essays. This is a descriptive quantitative research conducted by survey design. The population of this research was 107 of the fourth semester students of English Study Program FKIP Universitas Riau and all of it was appointed as the sample. The data were collected through a questionnaire containing 24 close-ended statements. The questionnaire was adaptred from Second Language Writing Anxiety Inventory (SLWAI) designed by Cheng (2004) and Causes of Writing Anxiety Inventory (CWAI) designed by Rezaei and Jafari (2014). The result of data analysis showed that the fourth semester students of English Study Program FKIP Universitas Riau felt anxious in drafting process of essay writing. The factors that contributed to that were: linguistic problems (18.02%), time pressure (17.75%), lack of topical knowledge (16.80%), and lack of vocabulary mastery (16.66%). Furthermore, it is recommended that students need to find out the factors that contribute to their writing anxiety and try to find the best way to cope with their anxiety. Students also need to do more practice in English essays writing and discuss their problems in writing with the lecturer. In line with that, the lecturer should create a comfortable situations in Writing class to make the students more relaxed in expressing ideas through writing and the lecturer also need to pay more attention in students’ problems of writing essays that can lead them to anxiety.Key Words: Writing, Anxiety, Writing Anxiety, Writing Essays